Evaluation of cases with toxicological findings in forensic autopsies conducted by the Department Of Forensic Medicine, Faculty Of Medicine, Sivas Cumhuriyet University, between 2017-2022 - Bütün, Celal; Yucel Beyaztas, Fatma; Can, Muhammet; Yildirim, Ali (The Bulletin of Legal Medicine, 2025)
Objective: Poisoning is a public health problem that causes significant morbidity and mortality worldwide. This study aims to identify the toxic agents that cause death at different times and in different geographic regions and to contribute to the reduction of poisoning cases by examining the characteristics of forensic cases.Method: Demographic characteristics of 55 cases in which alcohol and/or toxic substances were detected in 207 forensic autopsies performed at the Department of Forensic Medicine, Faculty of Medicine, University of Sivas between 2017 and 2022 were retrospectively analyzed.. Descriptive statistical analysis of the data was performed with the SPSS v.27 program using the Pearson and chi-square test.Results: It was determined that 81.8% of the cases were male, the youngest was two years old and the oldest was 84 years old, and the average age was 41.4. It was seen that the 31-40 age group was in first place with 25.5%. Among the 55 cases in which alcohol and toxic substances were detected, ethyl alcohol was the leading cause of death, with a rate of 29.6%. Poisonings were most common in the spring (36.4%). Hanging (18.2%) and carbon monoxide (14.5%) were the top two causes of death.Conclusion: In this study, the first three factors in the analysis of fatal poisoning cases were alcohol, therapeutic drugs and carbon monoxide. In order to prevent toxic deaths; the society should be informed about the dangers of fake/smuggled alcohol consumption, the necessary education to prevent unconscious drug use, control and social communication strengthening ...
Keywords: Forensic Medicine; Poisoning; Toxicology; Autopsy Data; Forensic Autopsy